The Effectiveness of the Electronic Collabortion Learning for Developing the Mathematical Proficiency among Pre-service Mathematics Teachers - Sallam, Shohwd Sharaf Gharsan; Saeed, Radman Mohamed (Journal of Educational and Psychological Sciences, 2023)
This study aimed to investigate the effects of the electronic collaboration learning for developing the mathematical proficiency among pre-service mathematics teachers. To achieve this aim, the researchers used experimental approach that was designed for two groups: experimental and control group. The sample of this study consisted of (63) pre-service mathematics teachers in faculty of education-Sana'a. They were distributed to the experimental group that consisted of (31) and control group that consisted of (32). The study tools consisted of mathematical proficiency test and productive disposition toward mathematics scale. To treat data statistically, the data was analyzed by using Mann-Whitney Test (U) and T-Test. The study results showed a statistical significance difference at the level (0.05) between the mean rank scores of the experimental group and the control group in the mathematical proficiency test in favor of the experimental group, where there is no statistical significance at the level (0.05) between the mean of the experimental group and the control group in the productive disposition toward mathematics. According to the result, the researchers recommended design training courses and workshops for mathematics teachers to train them how to use electronic collaboration learning in the teaching and learning process.
Keywords: collaboration learning; electronic learning; mathematical proficiency; mathematics teachers; pre-service teacher